Effect of Saccharomyces cerevisiae and fermentation times on the chemical composition of oat and barley silage - Fernandez Taype, Ricardo (2021)
The aim of this study was to evaluate the effects of the yeast Saccharomyces cerevisiae as an additive for the preparation of oat and barley silage in two fermentation times (21 and 42 days). Oat and barley minisilos were prepared using four levels of yeast (0, 15, 30 and 45 g/kg FV). The minisilos were opened at 21 and 42 days. Three silage replicates were prepared for each combination of silage x yeast level x silage time. The bromatological composition values of the oat silage in terms of crude protein (CP), mineral matter (MM), neutral detergent fibre (NDF), acid detergent fibre (FDA), ethereal extract (EE) and pH increased when the yeast was added in relation to the control, but the dry matter (DM) decreased. The quality of the barley silage in terms of DM, CP, NDF, FDA and EE improved when adding 30 and 45 g/kg of yeast, compared to the control; however, it decreased for EE and pH. The results show that the inoculation of S. cerevisiae in the two fermentation times increases the content of CP, EE, MM and pH of the silage; nevertheless; the high pH level does not allow proper conservation of the quality of the silage. It is concluded that the best nutritional values were obtained with the addition of S. cerevisiae of 45 g/kg at 42 days of fermentation in both silages, although it decreases some important parameters.